Lactate Levels in a Replanted Limb as an Early Biomarker for Assessing Post-Surgical Evolution: A Case Report - Alina Belu; Viorel Țarcă; Nina Filip; Elena Țarcă; Laura Mihaela Trandafir; Rodica Elena Heredea; Silviana Chifan; Diana Elena Parteni; Jana Bernic; Elena Cojocaru (Diagnostics)
Background and Clinical Significance: In the clinical management of major pediatric traumatic injuries and other hypoxic conditions, lactate is widely recognized as a key indicator of tissue hypoxia and potential necrosis. However, its prognostic value remains uncertain. Several factors influence post-surgical outcomes, including the time between amputation and replantation, transport conditions, asepsis, the extent of tissue necrosis, hemorrhagic shock, coagulation disorders, and the heightened risk of contamination. Case presentation: We present this case to emphasize the utility of systemic lactate versus lactate levels in the replanted limb for monitoring post-transplantation outcomes in a pediatric patient with traumatic limb amputation. Significant fluctuations in lactate levels within the replanted limb were observed at the onset of unfavorable evolution, specifically on the seventh postoperative day, coinciding with the identification of Aspergillus spp. infection. This necessitated the use of synthetic saphenous vein grafts and Amphotericin B administration. Despite these interventions, disease progression ultimately led to limb amputation. Conclusions: Lactate levels in the replanted limb may serve as an early biomarker for assessing post-surgical evolution. However, further case reports are required to confirm its predictive value.